Avian Chaperonin Containing TCP1 Subunit 5 Supports Influenza A Virus Replication by Interacting With Viral Nucleoprotein, PB1, and PB2 Proteins - Zhang, Xiaohan; Lin, Xian; Qin, Chenghuang; Huang, Kun; Sun, Xiaomei; Zhao, Lianzhong; Jin, Meilin (Frontiers in Microbiology, 2020)
Humans and avian species are prone to influenza viral infection, which may cause serious clinical consequences. Many studies have documented the critical role of host factors in the influenza virus life cycle based on human models, but knowledge about their roles in birds is very limited. In this study, using immunoprecipitation coupled with mass spectrometry, a total of 72 potential interacting proteins of influenza nucleoprotein (NP) were identified in DF-1 cells. Among these proteins, avian CCT5, a chaperonin containing TCP1 subunit 5, was demonstrated to interact with influenza A virus NP directly as well as PB1 and PB2, but not with PA. Further investigation showed that viral infection profoundly elevated the expression level of cellular CCT5, whose expression, in turn, promoted the nuclear export of NP as well as viral polymerase activity, thereby facilitating the replication of influenza A virus. The obtained results suggested an important role of avian CCT5 in supporting influenza virus replication, which may serve as an anti-influenza target.